Methyleugenol, a major metabolite on culture of endophytic fungi isolated from pandan wangi plant - Yuliasri Jamal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Two kinds of endophytic fungi i.e. Colletotricum sp. PWD2 and Coelomycetes PWA1 isolated from pandan wangi (Pandanus amarylifolius) have been cultivated in a liquid medium, GYP for 3 weeks at room temperature without agitation. The ethyl acetate extracts derived from liquid cultures showed antifungal activity against Saccharomyces cerevisiae. The GC-MS analysis results showed methyleugenol as main metabolite in the ethyl acetate extract of both fungi cultures.Key words: pandan wangi, Pandanus amarylifolius, endophytic fungi, antifungal, methyleugenol